Parents' Perceptions of Children's Learning Activities At Home during the Covid-19 Pandemic in Gang Serasi, Berastagi District - Elizon Nainggolan; Kevin Josua Kanta; Rosdiana Rosdiana; Mahfuzi Irwan (Budapest International Research and Critics University, 2022)
This research is motivated by the problem of how parents perceive their children's learning activities at home during the Covid-19 pandemic in Gang Serasi, Berastagi District. The purpose of this study was to find out an overview of parents' perceptions of their children's learning activities at home during the Covid-19 pandemic in Gang Serasi, Berastagi District. The type of research used is descriptive with a quantitative approach. The sample in this study amounted to 40 people. Sampling using total sampling technique. The data collection tool used was a questionnaire and the data were analyzed using data descriptions and trend testing. The results showed that the parental perception variable on the cognitive, affective, and conative indicators as a whole was at an average score of 2.41 with a low interpretation. The results of the trend test of the research variables showed that the research variables were at a very low tendency with the largest number of respondents, namely 62.5%. The conclusion in this study is that parents' perceptions of children's learning activities at home during the Covid-19 pandemic in Gang Serasi, Berastagi District based on cognitive, affective, and conative indicators are in low interpretation criteria. That is, parents consider children's learning activities at home to cause children to not understand learning, learning activities are not effective, children tend to be lazy in doing assignments, and parents are burdened because they have to teach children at home and supervise them.